Analisis Kepuasan Konsumen pada Sayuran Organik di Pasar Swalayan - Dewi Nopita Sari; Ismalia Afriani; Zulkarnain Zulkarnain; Ainul Mardliyah; Maryati Maryati (Universitas Islam Bandung, 2020)
ABSTRACT This study aims to determine the level of consumer satisfaction with organic vegetables in supermarkets. The location of this research is in Tanjung Karang Supermarkets. Respondents in the study were 30 consumers of organic vegetables in Tanjung Karang Swalayan who were determined by accidental sampling technique (Accidental sampling). The research objective was to determine consumer satisfaction with organic vegetables in supermarkets. The analysis used is the Customer Saticfactions Index (CSI) and Importance Performance Analysis (IPA) analysis. The results obtained are the level of consumer satisfaction of organic vegetables at Tanjung Karang supermarket is classified as satisfied. Meanwhile, from the results of the Importance Performance Analysis (IPA) analysis, the level of consumer interest is slightly greater than the performance level attribute that the company provides. This shows that the level of company performance has not met the expectations desired by consumers. Keywords: Satisfaction, Consumers, Vegetables, Organic, Supermarket ABSTRAK Penelitian ini bertujuan untuk mengetahui tingkat kepuasan konsumen terhadap sayuran organik di swalayan. Lokasi penelitian ini di Swalayan Tanjung Karang. Responden dalam penelitian adalah konsumen sayuran organik di Swalayan Tanjung Karang sebanyak 30 orang yang ditentukan dengan teknik sampel accidental (Accidental sampling). Tujuan penelitian adalah untuk mengetahui kepuasan konsumen pada sayuran organik di swalayan. Analisis yang digunakan adalah analisis Customer Saticfactions Index (CSI) dan Importance Performance Analisys (IPA). Hasil penelitian yang didapatkan adalah tingkat kepuasan konsumen sayuran organik di Swalayan Tanjung Karang tergolong puas. Sedangkan, dari hasil analisis Importance Performance Analisys (IPA) tingkat kepentingan konsumen sedikit lebih besar dari pada atribut tingkat kinerja yang perusahaan berikan. Hal ini menunjukkan bahwa tingkat kinerja perusahaan belum memenuhi harapan yang diinginkan oleh konsumen. Kata kunci: Kepuasan, Konsumen, Sayuran, Organik, Supermarket